Early Auditory Experience Modifies Neuronal Firing Properties in the Zebra Finch Auditory Cortex - Kudo, Takashi; Morohashi, Yuichi; Yazaki-Sugiyama, Yoko (Frontiers in Neural Circuits, 2020)
Songbirds learn to sing much as humans learn to speak. In zebra finches, one of the premier songbird models, males learn to sing for later courtship through a multistep learning process during the developmental period. They first listen to and memorize the song of a tutor (normally their father) during the sensory learning period. Then, in the subsequent sensory-motor learning phase (with large overlap), they match their vocalizations to the memorized tutor song via auditory feedback and develop their own unique songs, which they maintain throughout their lives. Previous studies have suggested that memories of tutor songs are shaped in the caudomedial nidopallium (NCM) of the brain, which is analogous to the mammalian higher auditory cortex. Isolation during development, which extends the sensory learning period in males, alters song preference in adult females, and NCM inactivation decreases song preference. However, development of neurophysiological properties of neurons in this area and the effect of isolation on these neurons have not yet been explained. Here, we performed whole-cell patch-clamp recording on NCM neurons from juvenile zebra finches during the sensory learning period, 20, 40 or 60 days post-hatching (DPH) and examined their neurophysiological properties. In contrast to previous reports in adult NCM neurons, the majority of NCM neurons of juvenile zebra finches showed spontaneous firing with or without burst firing patterns, and the percentage of neurons that fired increased in the middle of the sensory learning period (40 DPH) and then decreased at the end (60 DPH) in both males and females. We further found that auditory isolation from tutor songs alters developmental changes in the proportions of firing neurons both in males and females, and also changes those of burst neurons differently between males that sing and females that do not. Taken together, these findings suggest that NCM neurons develop their neurophysiological properties depending on auditory experiences during the sensory song learning period, which underlies memory formation for song learning in males and song discrimination in females.